Modelling the transport of toluene liquid in protective polymer gloves using a fluorescent dye-tracing technique. (May 2015) - Chen, Ming-Jen; Cheng, Li-Hsin; Tseng, Tzu-Ping; Huang, Yong-Sheng; Lin, Ching-Ho; Lai, Chin-Hsing
Graphical abstract: Schematic showing the proposed model with a 3D diagram for the mass transfer mechanism of toluene liquid through polymer gloves at steady state. Highlights: A dye-tracing technique was used to probe the mass transfer of toluene liquid across polymer gloves. An evidence-based model for the mass transfer is proposed. The model comprises three regimes of liquid, combined liquid–vapour, and vapour phases of toluene within the membrane. Abstract: The absence of adequate information about the phase change of liquid solvents within polymer-glove walls hinders the complete characterisation of the mass transfer of toluene liquid through the polymer membranes using the data obtained from ASTM F739 method for toluene liquid permeation testing. Therefore, an alternative fluorescent dye-tracing technique is used to account for the transport processes of toluene liquid through polymer gloves. The results of dye penetration experiments show that the displacement of liquid-phase toluene is proportional to the square root of immersion time, indicating that the transport behaviour of liquid-phase toluene is dominated by Fickian diffusion. Furthermore, a linear relationship between the mass sorption of toluene vapour and the sampling time is established, which suggests that the diffusion process in the vapour-phase toluene is governed by Case-II transport. Based on the combined analysis of the results obtained from permeation tests, immersion tests, fluorescent dye-tracer tests, and the pertinent calculations of thermodynamic properties, an evidence-based mechanism for the mass transfer of toluene liquid through the polymer-glove walls is proposed in terms of time-series processes. The model comprises three regimes: a liquid phase, a combined liquid–vapour phase, and a vapour phase of toluene that exist in series within the membrane.